Calcium phosphate bone filling materials: synthesis, hardening and characterization - Alqap, Asep Sofwan Faturohman (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Calcium phosphate based materials are clinically accepted ceramics and have been widely used in biomedical application. Apart from brittleness, calcium phosphate ceramics are introduced in the forms of coating, porous, granule, dense, powder and paste. Various methods have been developed to produce calcium phosphate ceramics for bone filler application. This work developed a novel technique which straightforwardly provided the calcium phosphate as bone filling materials from one pot low temperature hydrothermal synthesis. Calcium oxide, CaO, and ammonium dihydrogen phosphate, NH4H2PO4, were used as calcium and phosphorus precursors respectively with the media of stirred distilled water at 80-100°C. The amount of CaO was varied at 0, 1, 2, 10 and 20 mol-% excess. Synthesis condition has shown remarkable effects on phase, crystal physics, mechanical strength, hardening by aging in moist and simulated body fluid (SBF) environments, water washout resistance, cohesivity, injectability, bioactivity and Vero cell proliferation capacity. The characterization involved X-ray diffraction (XRD), energy dispersive X-ray (EDX), thermogravimetry/differential thermal analyses (TGA/DTA), Fourier transform infra red spectroscopy (FTIR), scanning electron microscopy (SEM) and Brunnauer-Emmet-Teller (BET) methods. Bone fillers were produced through two types of strategies: mixing between the precipitated powder, p, and water, w, (called as Mixture) at variation of p/w ratios and direct synthesis (called as Paste). The syntheses resulted in non crystalline apatite or Ca-deficient hydoxyapatite (CDHA) as the main phase of the non sintered product in all the excess CaO variations. The maximum compression strength after aging for Mixture was 2.0 MPa in the moist and 3.4 MPa in SBF, while for Paste, it was 2.3 MPa in the moist and 2.7 MPa in SBF. Paste showed as better performance in aspects of mechanical strength, resistance to watering, less fluctuation of the lattice crystal after aging and being injectable after 60 min waiting time. The precursors regulated the products to be single, non-single phase or potential as the candidate of antibacterial material. The apatite cell forming capacity that was affected by the pressure of the pellet compaction was also reported. The study showed that the filler materials are mechanically and biochemically suitable for non-load bearing bone implant applications and Paste is excellent in flexible handling time.